0111 The Hils Have Eyes. (1st November 2014) - Riby, Stuart; Gay, Chris; Graby, Matthew; Purva, Makani
Abstract : Background: How HILS have been integrating eye tracking technology into simulation based training. This introduced many technological opportunities and challenges. A look at how the need for further training in human factors led to the purchase of the eye tracking technology. Research has been carried out from a training perspective and a technical perspective. The complexity of the technology meant much training and testing has been implemented and has led to some tech hybrid simulation based training in cardiology and anaesthetics. Innovations: The development of the streamlining of the technology to make it more accessible for users – replacing large laptop with tablet device and an easier way of wearing the technology to increase mobility. Pairing the eye tracking technology in simulation training along with Laerdal SimMan 3G and the Simbionix Angiomentor for hybrid technology enhanced training. Outcomes: Ability to export video and data to analyse candidates behaviour and focus in clinical situations. Enhancement of skills for tech team and other operators with this extremely advanced technology. The integration of eye tracking technology in the training of clinicians and research at Hull and East Yorkshire Hospitals NHS Trust and the Yorkshire and Humber region. Take-home messages: The potential use of this and other advanced technology such as eye tracking in the future of clinical training and research? How we have merged this technology with our existing systems. How we learnt to use this technology to suit our centre's needs. Reference: Makani Purva